Leveraging AI to Optimize English Academic Writing (EAW) in Intelligent Decision Support Systems (IDSS) - Marmoah, Sri; Adika, Dimas; Haryati, Sri; Yurni, Yurni (Universitas Batanghari Jambi, 2024)
Many students and academics face difficulties in English academic writing, particularly non-native speakers of English. This paper examines the use of Artificial Intelligence (AI) in optimizing English academic writing in intelligent decision supporting systems (IDSS). Various literatures were studied to find out how AI can help improve English academic writing. The findings reveal that AI can improve grammar, spelling, sentence construction and make suggestions for clarity and cohesion through tools like Grammarly. Furthermore, integrating AI into IDSS also promotes more efficient and data driven decisions. However, there are still barriers like complex data analysis, ensuring accuracy and reliability of AI-generated content, and addressing ethical issues including bias and transparency. This simple paper highlights the importance of developing more sophisticated and user-friendly AI technologies and the need for further research to explore the long-term impact of using AI in English academic writing for Indonesia context. The results are beneficial to learners, educators and learning institutions as they employ AI tools with the purpose to improve the English academic writing quality and support better decision making.